Penguatan Kapasitas Pokdarwis untuk Pariwisata Berkelanjutan Berbasis Kearifan Lokal di Pesawaran, Lampung (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
This community service program aimed to strengthen the capacity of local communities in managing sustainable tourism in Pesawaran Regency, Lampung Province. The initiative was motivated by the region's rich natural and cultural tourism potential, which has not yet been matched by adequate community understanding, institutional capacity, and sustainable practices. The program employed a participatory approach, including socialization, training, mentoring, and evaluations using pre- and post-program indicators. Target participants comprised Pokdarwis (tourism awareness groups), local business actors, village officials, and community leaders. Findings indicate significant improvements in understanding sustainable tourism, institutional capacity, environmentally friendly practices, utilization of local wisdom, and community participation. The program also fostered collective awareness regarding the importance of socially, economically, and environmentally sustainable destination management. Implications extend beyond individual behavior changes to the strengthening of local governance and community readiness to develop community-based tourism destinations. Overall, this initiative contributes to the development of a community empowerment model that supports regional sustainable tourism policies and has potential for replication in other areas with similar characteristics.